Answer:
E
Step-by-step explanation:
When you substitute (5,-19) for A you get -19=-21 which is incorrect, when you substitute it for B you get, -19=-13 which is also incorrect, for C you get -19=-14, D you get -19=-22, and finally for E you get the correct answer which is -19=-19. Hope this helps :)
Answer:
0
Step-by-step explanation:
0, it is a flat line on a graph
<h3>x is 2 and y is -2</h3>
<em><u>Solution:</u></em>
Given that,
3x-2 equal x-y equals 4
Which means,
3x - 2 = x - y = 4
Therefore,
x - y = 4
Also,
3x - 2 = 4
Simplify above expression
3x - 2 = 4
3x = 4 + 2
3x = 6
Divide both sides by 3
x = 2
Substitute x = 2 in x - y = 4
2 - y = 4
y = 2 - 4
y = -2
Thus x is 2 and y is -2